The level of understanding on the importance of estate management among the Muslim community in Selangor / Jannatul Aliesya Mohd Yusof and Muhamad Zuhaili Saiman - Mohd Yusof, Jannatul Aliesya; Saiman, Muhamad Zuhaili (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2024)
In Islam, property management is divided into two phases: management during life and after death. Estate management refers to handling property after a Muslim’s death, with the division of inheritance explicitly outlined in Islam. However, many estates worth millions of ringgits have reportedly been abandoned or poorly maintained after the owner's death, leading to a wasted inheritance that could have supported family members or heirs. This paper aims to assess the level of awareness and knowledge among the Muslim community regarding estate management. The study focuses on Muslims in Selangor, using a quantitative research design. Data was collected from respondents across all nine districts in Selangor through a random sampling method. The findings reveal a need for increased awareness and understanding of inheritance management within the community. Additionally, it highlights the necessity for agencies responsible for estate management to improve their processes, making it easier and quicker for the deceased's family to apply for inheritance.